FEATURES OF THE INTERNAL AUDIT OF MATERIAL VALUES IN HIGHER EDUCATION INSTITUTIONS - E., Sindarov Sh. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In this article, the auditing methods and procedures used in the internal audit of tangible assets in higher education institutions, in particular, the content of the inventory method used in this process, the characteristics of the inventory method, and the relevance of conducting research in this field are revealed. In the "discussion" part of the article, the opinions expressed by the economists who conducted scientific research on this topic, their scientific views, and the aspects of their opinions different from the author's scientific ideas are highlighted on the basis of theoretical opinions. In this, the sources reflecting the ideas of each economist who conducted research on the topic of the article are reflected in detail. Also, in the article, the characteristics of the internal audit of tangible assets are described on the basis of the author's scientific research on the example of higher education institutions. The article describes the important tasks of the internal audit of tangible assets in higher educational institutions, the tasks of the inventory commission on tangible assets, the inventory stages in the internal audit process, and the issues of improving the inventory process in the internal audit. At the end of the article, the researcher summarized the scientific and practical conclusions within the topic, and formulated relevant scientific and practical recommendations. The list of literature used in the formation of the content of the article is reflected based on the established order.